Karyopherin β2 mediates nuclear import of a mRNA binding protein - Bonifaci, Neris (The National Academy of Sciences of the USA, 1997)
We have cloned and sequenced cDNA for human karyopherin β2, also known as transportin. In a solution binding assay, recombinant β2 bound directly to recombinant nuclear mRNA-binding protein A1. Binding was inhibited by a peptide representing A1’s previously characterized M9 nuclear localization sequence (NLS), but not by a peptide representing a classical NLS. As previously shown for karyopherin β1, karyopherin β2 bound to several nucleoporins containing characteristic peptide repeat motifs. In a solution binding assay, both β1 and β2 competed with each other for binding to immobilized repeat nucleoporin Nup98. In digitonin-permeabilized cells, β2 was able to dock A1 at the nuclear rim and to import it into the nucleoplasm. At low concentrations of β2, there was no stimulation of import by the exogenous addition of the GTPase Ran. However, at higher concentrations of β2 there was marked stimulation of import by Ran. Import was inhibited by the nonhydrolyzable GTP analog guanylyl imidodiphosphate by a Ran mutant that is unable to hydrolyze GTP and also by wheat germ agglutinin. Consistent with the solution binding results, karyopherin β2 inhibited karyopherin α/β1-mediated import of a classical NLS containing substrate and, vice versa, β1 inhibited β2-mediated import of A1 substrate, suggesting that the two import pathways merge at the level of docking of β1 and β2 to repeat nucleoporins.